Journalism in the data age - Tong, Jingrong (SAGE Publications, 2022)
Journalism today is entwined with the digital. Stories can come from crowdsourcing and content farms. They can incorporate data visualisations and virtual reality. Journalists can find themselves working as self-employed digital entrepreneurs or for tech giants like Google and Facebook.